Understanding the residual nature of the freedom to provide services: Delineating the scope of application - Savković Vladimir (Anali Pravnog Fakulteta u Beogradu)
Freedom to provide services is specific in relation to rest of the fundamental freedoms of the European Union (EU) internal market in a way that, save for certain specific situations, it applies to cross-border activities of a commercial nature only in situations in which (provisions regulating) other freedoms are not applicable. Apparently, this so-called "residual nature" of the freedom to provide services makes understanding the borderlines between free provision of services and the rest of fundamental freedoms of the EU internal market even more important, since it causes additional need for establishing such difference in various situations. This article aims to provide additional guidance in that regard. It does so primarily in the context of the ratione materiae scope of application, by scrutinizing some of the most relevant case law of the Court of Justice of the European Union (CJEU) and offering corresponding comments and conclusions.